Improving Youth’s Outdoor Spaces in Public Housing Areas - Sazali, Muhammmad Iqram; Aminuddin , A M R; Awaluddin, Zuraina Leily; Shukri, Sharyzee Mohmad (MAJ - Malaysia Architectural Journal, 2021)
Youth are like the future of a country. Therefore, it is very important for us to make sure the young grow up smart and have great values that will contribute to the development of the future. Cities in Malaysia are becoming denser and denser as people move in to search for a better life. Plenty of literature materials have been published discussing matters that are related with this subject. This study utilizes that advantage through qualitative method of systematic literature review by gathering all the relevant literature materials from multiple sources such as journals, website, and books and analyse them in finding the relationship between youths and outdoor spaces especially in public housing areas in Malaysia. Analysis shows that outdoor spaces in Malaysia’s public housing development is lacking and is highly demanded by the residents, especially the youths. Outdoor space allows for social activities and interaction to happen thus creating a sense of neighbourhood in an area. This is essential to reduce anonymity between the residents and create a sense of community within a residential development. Even though there is a policy of providing 10% green space for a residential development, it is clearly not sufficient for the residents and further investigation needs to be done to improve the life especially of the urban poor living in the cities.